Analysis of marketing communication policy in banking institutions of Ukraine - Zaslavska Olha; Заславська Ольга (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2022)
Abstract. Marketing communications are an integral element of ensuring the bank's competitive position in the financial services market. In modern conditions it is not enough for financial institutions to develop a qualitatively new product, set an optimal price for it and choose effective distribution channels. Any financial institution must successfully operate the communication tools. Thus, the majority of the institution's communication costs are investments in the creation of intangible marketing assets: trademarks, relationships with consumers and other participants in the value chain. The implementation of the adopted communication strategy contributes to the development of organizational knowledge and a deeper understanding of the market, which allows the institution to increase the efficiency of the main business processes. For their part, these processes contribute to increasing the institution's potential to increase its shareholder value. In order to study the communication policy of Ukrainian banks, it was made a ranking of these institutions according to key financial and organizational indicators. Taking into account the analysis, the TOP-5 banks were selected for further research, which consists of an analysis of media activity of these commercial banks, website traffic indicators and their activity in social networks. Overall the following indicators were explored: number of messages about the banks on Facebook, in the printed and electronic media, on the websites of state authorities, on television and radio; the place of the bank's website by attendance, the average number of visits during one month, the average length of stay on the site, the average number of viewed pages and the bounce rate. As a conclusion it was emphasized on the need in further research of this topic in the field of anti-crisis communication management and there were outlined the directions of bank marketing in the period of an unstable economic situation. These directions will help to avoid a decline in sales in the difficult economic situation that is currently taking place in the Ukrainian financial market.

Резюме. Маркетингові комунікації є невід'ємним елементом забезпечення конкурентної позиції банку на ринку фінансових послуг. У сучасних умовах фінансовим установам недостатньо розробити якісно новий продукт, встановити на нього оптимальну ціну та вибрати ефективні канали збуту. Будь-яка фінансова установа повинна успішно працювати з інструментами комунікації. Таким чином, більшість комунікаційних витрат установи становлять інвестиції у створення нематеріальних маркетингових активів: торгових марок, відносин зі споживачами та іншими учасниками ланцюжка створення вартості. Реалізація прийнятої комунікаційної стратегії сприяє розвитку організаційних знань і глибшому розумінню ринку, що дозволяє установі підвищити ефективність основних бізнес-процесів. Зі свого боку, ці процеси сприяють збільшенню потенціалу установи для збільшення її акціонерної вартості. З метою вивчення комунікаційної політики українських банків було складено рейтинг цих установ за ключовими фінансовими та організаційними показниками. За результатами аналізу було відібрано ТОП-5 банків для подальшого дослідження, яке складається з аналізу медіаактивності цих комерційних банків, показників відвідуваності вебсайтів та активності в соціальних мережах. Загалом досліджувалися такі показники: кількість повідомлень про банки у Facebook, у друкованих та електронних ЗМІ, на сайтах органів державної влади, на телебаченні та радіо; місце сайту банку за відвідуваністю, середньою кількістю відвідувань протягом місяця, середньою тривалістю перебування на сайті, середньою кількістю переглянутих сторінок і показником відмов. Як висновок було наголошено на необхідності подальшого дослідження даної теми у сфері антикризового комунікаційного менеджменту та окреслено напрям банківського маркетингу в період нестабільної економічної ситуації. Ці напрями допоможуть уникнути падіння продажів у складній економічній ситуації, яка зараз склалася на фінансовому ринку України.

A marketingkommunikáció szerves részét képezi a bank versenyhelyzetének biztosításában a pénzügyi szolgáltatások piacán. Jelen helyzetben nem elég, ha a pénzintézetek minőségileg új terméket fejlesztenek ki, annak optimális árat határoznak meg, és hatékony értékesítési csatornákat választanak. Minden pénzintézetnek sikeresen kell dolgoznia a kommunikációs eszközökkel. Így az intézmény kommunikációs költségeinek nagy részét az immateriális marketingeszközök: védjegyek, fogyasztókkal és az értéklánc más szereplőivel való kapcsolattartásba történő befektetések teszik ki. Az elfogadott kommunikációs stratégia megvalósítása hozzájárul a szervezeti ismeretek fejlesztéséhez és a piac mélyebb megismeréséhez, amely lehetővé teszi az intézmény számára a fő üzleti folyamatok hatékonyságának növelését. Ezek a folyamatok a maguk részéről hozzájárulnak ahhoz, hogy növeljék az intézmény lehetőségeit a részvények értékének növelésében. Az ukrán bankok kommunikációs politikájának tanulmányozása érdekében a legfontosabb pénzügyi és szervezeti mutatók alapján összeállítottuk ezen intézmények minősítését. Az elemzés eredményei alapján TOP-5 bankot választottunk ki a további kutatásra, ami ezen kereskedelmi bankok médiaaktivitásának, a weboldallátogatások és a közösségi oldalakon való aktivitás mutatóinak elemzéséből áll. Általánosságban a következő mutatókat vizsgáltuk: a bankokról szóló üzenetek számát a Facebookon, a nyomtatott és elektronikus médiában, az állami hatóságok weboldalain, a televízióban és a rádióban; a bank weboldalának látogatottságát, átlagos látogatások számát a hónap során, átlagos tartózkodási időt az oldalon, átlagosan megtekintett oldalak számát és a visszavonási arányt. Konklúzióként hangsúlyoztuk a téma további kutatásának szükségességét a kommunikációs válságmenedzsment területén, és körvonalaztuk a bankmarketing irányát bizonytalan gazdasági helyzetben. Ezek a területek segítenek elkerülni az eladások visszaesését jelenleg az ukrán pénzügyi piacon uralkodó nehéz gazdasági helyzetben.
Аналіз маркетингової комунікаційної політики у банківських установах України
Marketingkommunikációs politika elemzése Ukrajna bankintézeteiben
https://aab-economics.kmf.uz.ua/aabe/issue/view/1
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00010507
Keywords: bank; marketing; communications; communication policy tools; anti-crisis communications